DESIGN AND DEVELOPMENT OF A TONG GLINDING SIMULATOR BASED ON VIRTUAL REALITY AS A MEDIUM FOR PHYSICS EDUCATION - Syahputra, Dimas Novian Aditia; Panduman, Yohanes Yohanie Fridelin; Dermawan, Dodik Arwin; Sidhimantra, I Gde Agung Sri; Hakim, Septian Rahman (Jurnal INSTEK (Informatika Sains dan Teknologi), 2025)
Physics learning about motion concepts is often abstract, while traditional games with embedded scientific principles are increasingly overlooked. This study addresses both issues by developing a Virtual Reality (VR)–based physics simulator inspired by the traditional Tong Glinding game. Designed as an interactive virtual laboratory, the simulator allows users to adjust the incline angle (1°–6°), choose a smooth or rough surface, and observe the motion of a rolling barrel along a 20-meter track. Developed using the Research and Development (R&D) method with the ADDIE model and implemented in Unity 3D, the system integrates cultural heritage with immersive VR experimentation. Functional testing confirmed 100% conformity to design specifications. Simulation verification demonstrated high accuracy, with errors of only 1.8%–2.5% between simulation and analytical calculations on the smooth surface, while the rough surface correctly produced no motion at low angles. User experience testing with 30 participants yielded a high overall score of 87.5 out of 100, supported by strong reliability across all dimensions (Cronbach’s α = 0.85–0.92). These results show that the simulator is technically reliable, physically accurate, and well-received as a learning medium. The combination of cultural preservation and interactive VR-based experimentation represents the novelty of this work.